The Effect of Digital Competence on Employee Performance: The Mediating Roles of Self-Efficacy and Job Satisfaction (A Case Study of the Tangerang City Regional Revenue Agency) - Artanti Dwi Rosadi; Wawan Prahiawan (Prosperia: Journal of Economic Development, Accounting, and Global Markets, 2026)
This study examines the influence of digital competence on employee performance through the mediating roles of self-efficacy and job satisfaction at the Tangerang City Regional Revenue Agency. Employing a quantitative research design with a saturated sampling technique involving eighty one employees, the data were analyzed using partial least squares structural equation modeling. The empirical results demonstrate that digital competence exerts a positive and significant direct effect on employee performance, self-efficacy, and job satisfaction. Furthermore, both self-efficacy and job satisfaction act as significant partial mediators in the relationship between digital competence and employee performance. These findings contribute to human resource management theory by highlighting cognitive and affective pathways in digital workplace transformation, while providing practical insights for public sector organizations seeking to optimize administrative efficiency and service delivery quality through targeted capability building and supportive work environments.